The Roots of Conflict: Mapping and Inter-Religious Conflict Resolution Mechanisms in Aceh Singkil - Zulfatmi, Zulfatmi; Mulia, Muji; Khalil, Zakki Fuad; Fairusy, Muhajir Al; Idria, Reza; Khatimah, Husnul; Faizah, Ade (Islam Futura, 2026)
This study aims to identify the root causes of interreligious conflict in Singkil at the grassroots level and to examine the mechanisms for conflict resolution in order to achieve mutual respect and prevent intolerance among religious adherents. The central argument of this research is that the emergence of sentiments and frictions among religious communities is driven by various factors, including differences in interfaith beliefs, politics, economics, ethnicity, and other forms of provocation that trigger conflict. The research seeks to map and categorize the root causes of conflict at the grassroots level and to explore the mechanisms for conflict resolution through various alternative conflict resolution approaches. This study employs a qualitative method, beginning with field observations and followed by in-depth interviews with key informants to uncover the causes of conflict and the mechanisms used for its resolution in the Singkil region. The findings indicate that the root causes of interreligious conflict stem from issues related to the establishment of houses of worship since the 1960s, differing interpretations of religious teachings, specific agendas that provoke conflict, the spread of misinformation, and provocative statements disseminated through social media alongside the advancement of information technology. Conflict resolution mechanisms have been implemented through cultural and customary approaches, deliberation and consensus, adherence to agreed-upon regulations and norms, the active and committed role of local government in addressing the conflict, and the development of mutual acceptance and respect among the conflicting parties